2020
DOI: 10.1002/arcp.1069
|View full text |Cite
|
Sign up to set email alerts
|

A review of the cognitive and sensory cues impacting taste perceptions and consumption

Abstract: Food has a daily impact on all consumers, requiring frequent evaluations and decisions pre‐consumption, during, and post‐consumption. Given the number of consumer interactions and the complexity of the food consumption process, researchers have increasingly studied food from both a sensory standpoint and cognitive standpoint. In this review, we create a framework for this existing research. Specifically, we discuss research addressing the key sensory drivers of taste perceptions and consumption, including all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 84 publications
2
26
0
1
Order By: Relevance
“…stimulus-type and number of exposures) under which proximal depictions affect consumer responses. In studying these effects, we extend the prior research on visual processing of images and their effect on food consumption behavior (Elder and Krishna, 2012;Poor et al, 2013;Krishna and Elder, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…stimulus-type and number of exposures) under which proximal depictions affect consumer responses. In studying these effects, we extend the prior research on visual processing of images and their effect on food consumption behavior (Elder and Krishna, 2012;Poor et al, 2013;Krishna and Elder, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…stimulus-type and number of exposures) under which proximal depictions affect consumer responses. In studying these effects, we extend the prior research on visual processing of images and their effect on food consumption behavior (Elder and Krishna, 2012; Poor et al , 2013; Krishna and Elder, 2021). This research provides further evidence that implicit and explicit attitudes are not completely aligned, even when social desirability issues are eliminated, and that our attitudes toward stimuli may be affected by learning through repetitive exposure (Karpinski and Hilton, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…A positive olfaction serves two key purposes – the priming of hedonic states and the priming of brand recall or information retrieval. Studies have found a privileged neural link between sections of the olfactory neural system and sensorial cortices of the brain linked to emotional memory (Biswas et al , 2021; Krishna and Elder, 2021). This connection predisposes the triggering of emotive memories and responses to olfaction signals, resulting in the accentuation of a priming effect (De Luca and Botelho, 2021).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Taste modality is unique because its efficacy depends on a whole range of parallel stimulation. When something is sensed as tasty, it is not just the sensations generated by receptors embedded in the tongue that are providing the information; receptors representing different modalities are also involved (Elder and Krishna, 2021; Krishna and Elder, 2021; Schlosser, 2015). Spence and Van Doorn (2017) highlighted the significance of this mouth/mind relationship by reminding us that the pleasures of the table reside in the mind rather than the mouth, while Roggeveen et al (2020) have argued that taste sensory cues are a key element of the trialability factor and consumer-perceived brand information after their taste sampling experience.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Yet, consumer psychology research indicates that communicating health and nutrition information can actually undermine healthy choices, with consumers anticipating less enjoyment from foods they believe are healthy (Gomez & Torelli, 2015; Krishna & Elder, 2021; Raghunathan et al, 2006; Suher et al, 2016). Indeed, research found that nutrition information reduced French consumers' assessment of the quality of food and their expected level of enjoyment of that food.…”
Section: Seed Frameworkmentioning
confidence: 99%